Implementation of Murabahah Financing Transactions at Islamic Commercial Banks After the Abolition of Value-Added Tax - Iwan Setiawan; Ahmad Mudzakir; Nurhaeti; Gina Sakinah; Ade Ponirah (Department of Islamic Economics, Islamic University of Indonesia, 2022)
The characteristics of Islamic banking that distinguish it from conventional banking are the basis of transactions associated with the real sector. This study aims to analyze the differences in murabahah financing transactions in Islamic commercial banks after the abolition of value-added tax. The population in this study was all Islamic commercial banks in Indonesia, with 14 samples using the saturated sample technique. This type of research data is secondary data obtained from Islamic banking performance reports on the official website of the Financial Services Authority. This research is a quantitative study with analysis using a paired-sample t-test utilizing IBM® SPSS® Statistics. The results showed differences in murabahah financing transactions after the abolition of value-added tax. The hypothesis is supported with a t-statistical value of 14,213 Sig. 0.000. It can be concluded that it is empirically proven that there are significant differences in murabahah financing transactions after the elimination of value-added tax. These results can be positive input for Islamic commercial banks to increase murabahah financing transactions after the abolition of value-added tax.